Evaluation of the seizure modifying potential of ondansetron in mice - Jadhav, Nisharani; Baradol, Ravikumar; Bhosale, Manisha (International Journal of Basic & Clinical Pharmacology, 2018)
Background: The aim of the study was to evaluate the seizure modifying potential of Ondansetron in experimental models of seizures in mice. Methods: Mice were treated with three different doses of ondansetron i.p., at 3mg/kg, 6mg/kg and 8mg/kg and control group received normal saline 0.1 ml i.p. for 3 days. On 3rd day, mice were subjected to MES, of different strength half an hour after ondansetron administration and findings were recorded. The minimum threshold current at which tonic hind limb extension occurred was recorded. Each animal was observed for incidence and duration of tonic hind limb extension and the strength of current was noted. In PTZ model, mice were subjected to subconvulsive dose of PTZ 45mg/kg and convulsive dose of PTZ 60mg/kg. The incidence and onset of convulsion at 45 and 60mg/kg dose of PTZ were recorded. Results: Mice receiving ondansetron 3mg/kg, showed significant decrease in duration of tonic hind limb extension at convulsive current strength of 50mA (p<0.001). While group receiving 6mg/kg, showed decrease in seizure threshold. (40mA current strength) Mice receiving 3mg/kg, showed significant increase in onset of seizures (p<0.001) at convulsive 60mg/kg dose of PTZ. While mice receiving 6mg/kg showed decrease in seizure threshold at sub convulsive 45mg/kg dose of PTZ. Group receiving 8mg/kg ondansetron, showed 100% mortality due to convulsions caused by ondansetron. Conclusions: Ondansetron at low therapeutic dose (3mg/kg) has an anticonvulsant action, while it has a proconvulsant action at a high therapeutic dose (6mg/kg). Ondansetron causes convulsions at toxic dose (8mg/kg). So, care should be taken while giving ondansettron in high doses to prevent chemotherapy induced emesis.